Embedded Philanthropic CSR in Digital China: Unified View of Prosocial and Pro-environmental Practices - Ye, Qing; Rafique, Zain; Zhou, Rongting; Asmi, Fahad; Anwar, Muhammad Azfar; Siddiquei, Ahmad Nabeel (Frontiers in Psychology, 2021)
In recent decades, China has been transformed from a conventional society into a digitally competitive nation. From an economic perspective, embedded corporate social responsibility (CSR) is gaining a new height where gamified charity is a trendy approach. By adopting the Norm Activation Model in the view of the stimulus–organism–response framework, this research theoretically conceptualized the role of the mobile application environment (includes telepresence, functional transparency, and accessibility) to map the cognition and philanthropic behavioral intentions of consumers in the gamified setting. The quantified survey comprised 669 respondents. Findings highlighted the critical role of a mobile application’s functional transparency and telepresence to drive consumers’ warm glow and ascribed responsibility. The research underlined the presence of the unique DNA of Internet Plus Charity (Public Benefits) for prosocial and pro-environmental purposes in China under the umbrella of philanthropic CSR.